Effects of temperature and atmosphere on microstructural evolution and mechanical properties of KD-II SiC fibers. Issue 15 (15th October 2020) - Yang, Chenxi; Wu, Jiejie; Ditta, Allah; Wei, Lijun; Zhao, Zihua; Wu, Sujun
Abstract: KD-II SiC fibers were heat treated from 800 °C to 1500 °C in argon and air atmospheres to comparatively analyze the effect of temperature and applied atmosphere on the microstructural evolution and mechanical behaviors of the fibers. The results show that sizes of the β-SiC grains, free carbon clusters, and micropores increase in both atmospheres as the temperature rises. Consequently, the strength of SiC fibers, in general, decreases with the increase in heat treatment temperature. However, SiC fibers responded differently during heat treatment at various temperatures in air compared to argon. The passive oxidation in air could cause more defects in the fibers. At 1200 °C, a lot of oxidation products were formed on the surface of the fibers; at 1400 °C, cracks appeared on the oxidation (silica) scale; and at 1500 °C, spallation of the oxide occurred. The cracking and spallation of the surface oxide may stem from the internal stress produced at the interface between the oxide scale and the unoxidized SiC core, which caused an earlier fiber failure in the air environment. As a result, the fiber strength treated in the air was lower than that treated in argon when the temperature was above 1200 °C.